Current Status of Chinese Medical Students’ Professional Identity After COVID-19 and the Factors That Influence It - Lai, Tinghong; Liang, Weidong; Zhong, Maolin; Zhu, Pingping; Li, Bin (Frontiers in Psychology, 2022)
This study aimed to explore the current situation regarding medical students’ professional identity after COVID-19 in China, as well as the factors that influence it. Questionnaire compiled by Fujian Medical University and self-designed were used, and participators were from one Medical University in Jiangxi Province, a central city of China. Results showed that the professional identity of medical students was upper middle level and the professional attitude was generally positive. There was a significant sex difference in terms of value (t = 2.057, p < 0.05) which the scores for boys were higher than girls, whereas the scores for girls were higher than boys when it came to aspects such as professional environment (t = -3.918, p < 0.001) and professional cognition (t = -3.855, p < 0.001). There was a significant difference in the sense of professional identity between people with and without siblings (t = 2.264, p < 0.05). The scores of students who participated in prevention and control of the epidemic were significantly higher than those who did not (t = 2.267, p < 0.01). Professional identity decreased gradually in related to higher grades, but it increased at the graduate stage; the grade [F (5,635) = 10.302, p < 0.001] and majors [F(2,635) = 5.718, p < 0.01] differences were significant. Factors such as family members’ influence, attitude toward occupation, grades, major, registered residence, and college choosing were the main factors that influenced medical students’ professional identity. Overall, the medical students’ professional identity needs to be further strengthened in the post COVID-19, it should be increased education regarding career development and planning.